WORLD'S WILDEST ANIMAL JOKES - Francis Murray (New York, United States Sterling Publishing Co Inc, 1993)
Includes hundreds of animal jokes arranged alphabetically from aardvarks to zebras
Keywords: Joke And Riddles -- Joke And Riddles